Persistent Intrathecal Antibody Synthesis 15 Years After Recovering From Anti–N-methyl-d-aspartate Receptor Encephalitis - Hansen, Hans-Christian (2013)
BACKGROUND: Anti–N-methyl-d-aspartate receptor (NMDAR) encephalitis is a severe autoimmune disorder characterized by high intrathecal antibody synthesis. Little is known about the long-term follow-up of the cerebrospinal fluid antibody status. OBJECTIVE: To describe persistent intrathecal antibody synthesis in a clinically healthy person 15 years after recovering from anti-NMDAR encephalitis. DESIGN: Case report. SETTING: Academic medical center. PATIENT: A 40-year-old woman who had been diagnosed as having encephalitis of unknown origin in 1995. MAIN OUTCOME MEASURES: Clinical evaluation and NMDAR antibody testing. RESULTS: On reexamination in 2011, the patient had fully recovered. Investigation of archived as well as follow-up serum and cerebrospinal fluid samples revealed intrathecal synthesis of NMDAR antibodies. CONCLUSIONS: This is the longest follow-up on a patient with anti-NMDAR encephalitis. Our findings emphasize that intrathecal antibody synthesis does not necessarily reflect disease activity and that the significance of NMDAR antibody titers needs to be interpreted for each patient according to the clinical context.